Axillary management in patients with clinical node-negative early breast cancer and positive sentinel lymph node: a systematic review and meta-analysis - Li, Changzai; Zhang, Pan; Lv, Jie; Dong, Wei; Hu, Baoshan; Zhang, Jinji; Zhu, Hongcheng (Frontiers in Oncology, 2024)
Background：The oOmission of axillary lymph node dissection (ALND) or axillary radiation (AxRT) in remains controversial in patients with clinical node-negative early breast cancer patients and a who has positive sentinel lymph node. is controversial. Methods：We performed conducted a comprehensive review by an extensive review by searching multiple databases such as PubmMed, Embase, Web of Science, and Cochrane databases (up to November 2023). TheOur primary main outcomes were measurements consisted of overall survival (OS), disease-free survival (DFS), locoregional recurrence (LRR), and axillary recurrence (AR). Results: We included 26 studies encompassing 145,548 women Twenty-six studies were included in this study, which included 145548 women with clinical node-negative early breast cancer and positive sentinel lymph node. Pooled data showed revealed no significant that there were not differences between ALND and sentinel lymph node biopsy (SLNB) alone in terms of OS (hazard ratio [HR]HR 0.99, 95% confidence interval [CI] 0.91-1.08, p=0.84), DFS (HR 1.04, 95% CI 0.90-1.19, p=0.61), LRR (HR 0.76, 95% CI 0.45-1.20, p=0.31), and AR (HR 1.01, 95% CI 0.99-1.03, p=0.35). Similarly, nNo statically significant differences waswere observed between AxRT and SLNB alone forin OS (HR 0.57, 95% CI 0.32-1.02, p=0.06) and DFS (HR 0.52, 95% CI 0.26-1.05, p=0.07). When comparing AxRT and ALND, a trend towards higher OS was observed estimated higher in the AxRT group compared to the ALND group (HR 0.08, 95% CI 0.67-1.15), but the difference wasdid not reach statistical significance not statistically significant (p=0.35, I 2 =0%). Additionally, no significant differences significanceThere were also no differences observed for in DFS orand AR (p=0.13 and p=0.73, respectively) in between the AxRT group versusand ALND groups.Our findings suggest that The survival and recurrence rates are not inferior in of patients with clinical node-negative early breast cancer and a positive sentinel lymph node who receive SLNB alone were not inferior compared to those who undergoing ALND or AxRT.